Analisis Percepatan Waktu Pelaksanaan Proyek Terhadap Rencana Anggaran Biaya Pada Proyek Pembangunan Kantor Dan Gedung Serbaguna Polresta Denpasar - Wahyu Guna, I Gede Putu; Ariana, Komang Agus (Jurnal Ilmiah Telsinas, 2020)
Time and cost greatly affect the success and failure of a project. The benchmark of project success is seen from a short turnaround time with minimal cost without leaving the quality of the work. The purpose of this research is to analyze the length of time of project implementation, bill of quantity, and percentage of cost plan after accelerated to normal project cost plan using the method of adding labor and overtime hours. The data used in this research is secondary data obtained from contractor implementing. Data analysis using the Microsoft Project 2016 program with the results obtained is the critical path, the duration per item of work, the time of project implementation as well as the total cost after the addition of labor and overtime hours. As a result of additional labor obtained 172 days with a total cost of Rp 6,611,384,715.00, get the difference of Rp 14,547,555 with percentage 0.22%, for additional hours of overtime work 1 hour obtained project time 154.39 days with total cost of Rp 6,638,980,929.00 get the difference of Rp 13,048,659.00 with percentage 0.20%, for the addition of 2 hours overtime was obtained at 116.06 days for a total cost of Rp 6,687,179,465.00 to get the difference of Rp 61,247,195.00 with 0.92% percentage, for the combination of additional labor and 1 hour overtime for 151 days with total cost of Rp 6,632,253,923 get difference of Rp 6,321,653.00 with percentage 0,10%, for combination of addition of labor and overtime hours 2 hours got time 114,54 day with total cost equal to Rp 6,682,351,473 get difference of Rp 56,419,203.00 with percentage 0,85 %.From the comparison of the addition of manpower, overtime and combination of additional labor and overtime hours, the time and cost of implementation are more efficient with no more than the duration and the normal cost budget plan that is to use the addition of manpower, with the result of 172 days and bill of quantityto Rp 6,611,384,715 from normal time of 210 days and normal budget plan of Rp 6,627,273,374.80.